Indirect Measurements of the Composition of Ultrafine Particles in the Arctic Late‐Winter. Issue 22 (18th November 2021) - Myers, Deanna C.; Lawler, Michael J.; Mauldin, Roy L.; Sjostedt, Steven; Dubey, Manvendra; Abbatt, Jonathan; Smith, James N.
Abstract: We present indirect measurements of size‐resolved ultrafine particle composition conducted during the Ocean‐Atmosphere‐Sea Ice‐Snowpack (OASIS) Campaign in Utqiagvik, Alaska, during March 2009. This study focuses on measurements of size‐resolved particle hygroscopicity and volatility measured over two periods of the campaign. During a period that represents background conditions in this location, particle hygroscopic growth factors ( HGF ) at 90% relative humidity ranged from 1.45 to 1.51, which combined with volatility measurements suggest a mixture of ∼30% ammoniated sulfates and ∼70% oxidized organics. Two separate regional ultrafine particle growth events were also observed during this campaign. Event 1 coincided with elevated levels of H2 SO4 and solar radiation. These particles were highly hygroscopic ( HGF = 2.1 for 35 nm particles), but were almost fully volatilized at 160 °C. The air masses associated with both events originated over the Arctic Ocean. Event 1 was influenced by the upper marine boundary layer (200–350 m AGL), while Event 2 spent more time closer to the surface (50–150 m AGL) and over open ocean leads, suggesting marine influence in growth processes. Event 2 particles were slightly less hygroscopic ( HGF = 1.94 for 35 nm and 1.67 for 15 nm particles), and similarly volatile. We hypothesize that particles formed during both events contained 60–70% hygroscopic salts by volume, with the balance for Event 1 being sulfates and oxidized organics for Event 2. These observations suggest that primary sea spray may be an important initiator of ultrafine particle formation events in the Arctic late‐winter, but a variety of processes may be responsible for condensational growth. Plain Language Summary: There are few measurements of ultrafine (sub‐100 nm) particle chemical composition in the Arctic, particularly during winter and early spring. This paper contains analysis of indirect measurements of ultrafine particle composition made in Utqiagvik, Alaska in March 2009. We focus on two periods during which local pollution was minimal to characterize both background and newly formed ultrafine particles. Our measurements suggest differences in composition between these two particle populations, indicating they likely formed from different sources. Analysis of the properties of the newly formed particles suggests that sea spray contributes to ultrafine particle formation in this region, which is unusual for the high Arctic during winter and spring, and that growth occurs from condensation of many different chemical species. Key Points: Indirect measurements suggest that background ultrafine particles are composed of oxidized organic species and ammoniated sulfates Two ultrafine particle growth events were observed and were likely influenced by marine emissions Newly formed particles were highly hygroscopic and relatively volatile, the latter property not consistent with primary sea salt aerosol